Brahmin capitalism : frontiers of wealth and populism in America's first Gilded Age - Maggor, Noam, 1977- (Harvard University Press, 2017)
Brahmin Capitalism explores the surprisingly dynamic role of established wealth in the rise of modern capitalism in the United States. Far from declining in prosperity and influence, elite Bostonians of illustrious lineage - the quintessential old money families on the American scene - successfully reinvented themselves. Better known as social reformers, philanthropists, and men of letters, these scions of wealth were also astute businessmen with immense financial resources. Venturing far afield from the comforts of the northeast, they painstakingly forged wide-ranging networks of capital, commodity, and labor flows that incorporated large territories in the American West into the economy of the United States. They played a decisive role in the reconstruction of the American economy during the decades after the Civil War, leading the way to the nationally-integrated corporate capitalism of the twentieth century.--